Mast cell–glia axis in neuroinflammation and therapeutic potential of the anandamide congener palmitoylethanolamide - Skaper, Stephen D. (The Royal Society, 2012)
Communication between the immune and nervous systems depends a great deal on pro-inflammatory cytokines. Both astroglia and microglia, in particular, constitute an important source of inflammatory mediators and may have fundamental roles in central nervous system (CNS) disorders from neuropathic pain and epilepsy to neurodegenerative diseases. Glial cells respond also to pro-inflammatory signals released from cells of immune origin. In this context, mast cells are of particular relevance. These immune-related cells, while resident in the CNS, are able to cross a compromised blood-spinal cord and blood-brain barrier in cases of CNS pathology. Emerging evidence suggests the possibility of mast cell–glia communication, and opens exciting new perspectives for designing therapies to target neuroinflammation by differentially modulating the activation of non-neuronal cells normally controlling neuronal sensitization—both peripherally and centrally. This review aims to provide an overview of recent progress relating to the pathobiology of neuroinflammation, the role of glia, neuro-immune interactions involving mast cells and the possibility that glia–mast cell interactions contribute to exacerbation of acute symptoms of chronic neurodegenerative disease and accelerated disease progression, as well as promotion of pain transmission pathways. Using this background as a starting point for discussion, we will consider the therapeutic potential of naturally occurring fatty acid ethanolamides, such as palmitoylethanolamide in treating systemic inflammation or blockade of signalling pathways from the periphery to the brain in such settings.